Na lidar measurements during the ECOMA/Geminids campaign with focus on Na peak density and temperature - Østerpart, Jørgen Olai Kristensen (Universitetet i Tromsø, 2011)
Using a resonance lidar, atomic Na (sodium) can be observed in the 80-110 km altitude range of the atmosphere. Na belongs to the alkali metal group and is highly reactive, so one could expect that it would quickly react with other particles and leave its atomic state. Its actual behaviour however includes the formation of relatively dense layers which, from the perspective of a stationary lidar, form suddenly and can last for several hours before quickly disappearing again. Several theories on the formation of these layers have been developed, including temperature dependent chemical processes, but none of them seem to explain all of the observed events. In 2008, two articles about these sudden sodium layers were published by scientists who have worked with the Weber Na lidar at the Arctic Lidar Observatory for Middle Atmosphere Research (ALOMAR), located at Andøya, Norway \((69^{°} 16' N, 16^{°} 00' E)\). Nesse et al. (2008) describe one particular Na layer observed 5 November 2005 and consider in turn how the most probable theories match the observed data during this event. Heinrich et al. (2008) identify all the sudden Na layers that have been observed on ALOMAR between August 2000 and June 2006 and investigate in particular how these coincide with sporadic E-layers (thin layers of several types of metallic ions). The fourth ECOMA (Existence and Charged State of Meteoric Smoke Particles in the Middle Atmosphere) rocket campaign took place at the Andøya Rocket Range during November and December 2010. The Na lidar was operated to the extent possible during this period, resulting in near real-time data for two of the three rocket launches and a total of 48 hours of measurements which are presented in this text. Using the two formerly mentioned articles as a starting point, I have studied available theory about sudden Na layers and the ALOMAR Na lidar in particular, and the upper atmosphere and resonance lidars in general. While we did not observe any sudden Na layers during the ECOMA measurements, I look ...